1985
DOI: 10.1037/0735-7028.16.6.741
|View full text |Cite
|
Sign up to set email alerts
|

Management of burnout: Training psychologists in professional life span perspectives.

Abstract: There is a keen awareness developing in psychology and other professions, supported by research findings, that many professionals (ire psychologically impaired and considerably underproduciwe in their work environment. A four-stage theory ofprofessiorud development is presented to highlight important developmental issues experienced by psychologists. It is proposed thai the growing research on burnout in professionals may be better understood in the context of a developmental theory. Suggestions are offered fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Considering the studies conducted about teachers, age and tenure are seen as the variables that affect on mathematics anxiety is searched. These studies showed parallel results (Garrosa, MorenoJimenez, Liang & González, 2008;Martinussen, Richardsen & Burke, 2007;Suran & Sheridan, 1984). Although some researchers determined that older teachers have higher mathematics anxiety levels than younger teachers (Betz, 1978;Dew, Galassi & Galassi, 1984), some researchers stated that there was a reverse relationship between mathematics anxiety and age and tenure variables (Byrne, 1994;Gold, 1985).…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…Considering the studies conducted about teachers, age and tenure are seen as the variables that affect on mathematics anxiety is searched. These studies showed parallel results (Garrosa, MorenoJimenez, Liang & González, 2008;Martinussen, Richardsen & Burke, 2007;Suran & Sheridan, 1984). Although some researchers determined that older teachers have higher mathematics anxiety levels than younger teachers (Betz, 1978;Dew, Galassi & Galassi, 1984), some researchers stated that there was a reverse relationship between mathematics anxiety and age and tenure variables (Byrne, 1994;Gold, 1985).…”
Section: Introductionsupporting
confidence: 48%
“…Again in parallel, Girgin (1995) reached the same result on primary teachers that anxiety decreases when age increases. Similar to these two studies, it is possible to encounter many studies which determine the result that anxiety decreases when age and tenure increases (Aslan et al, 1997;Byrne, 1994;Garrosa et al, 2008;Gold, 1985;Martinussen et al, 2007;Suran & Sheridan, 1984). The reason for this may be that people are more realistic when they are young but when they get older, they are more likely to speak as they are supposed to speak and answer as they are supposed to answer.…”
Section: Discussionmentioning
confidence: 98%
“…Burnout, or the depletion of physical and emotional resources resulting from the prolonged experience of stress (Suran & Sheridan, ), has garnered attention as a serious concern among psychologists (Rupert, Miller, & Dorociak, ; Smith & Moss, ), and school psychology practitioners more specifically (Huberty & Huebner, ; Huebner, ; Huebner, ). Although several conceptualizations of burnout have been offered in the literature, the model that has been most widely adopted by researchers examining the occupational functioning of human service professionals was proposed by Maslach and Jackson ().…”
Section: School Psychology: a Challenging Professionmentioning
confidence: 99%
“…In order to accomplish such a task, it is likely that greater attention needs to be devoted to the topic of burnout management among school psychology trainers at the preservice and inservice levels. With regard to preservice training, Suran and Sheridan (1985) have offered some provocative recommendations regarding changes in graduate psychology programs.…”
Section: Huebnermentioning
confidence: 99%